Impelementasi Metode Talaqi dan Murojaah Secara Halaqoh dalam Meningkatkan Motivasi dan Hasil Hafalan Santri di Ponpes Tahfidz Nurul Jihad Kota Bima - Silfatunnisa Rizkiyah; Luthfiyah Luthfiyah; Sri Jamilah (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to describe the implementation of the talaqi and murojaah methods within the halaqoh system as an effort to enhance students’ motivation and Qur’an memorization achievement at Pondok Pesantren Tahfidz Nurul Jihad, Bima City. This study employed a qualitative approach with a descriptive research design. Data were collected through participant observation, in-depth interviews, and documentation. The data analysis process followed the model of Miles, Huberman, and Saldaña, which consists of data condensation, data display, and conclusion drawing and verification. Meanwhile, data validity was strengthened through source triangulation, technique triangulation, and member checking. The findings indicate that the implementation of the talaqi and murojaah methods within the halaqoh-based system was carried out through three main stages. The first stage was planning, which included initial assessment and the grouping of students based on their Qur’an reading ability and memorization achievement. The second stage was implementation, which involved talaqi, ziyadah, memorization submission, and scheduled murojaah activities. The third stage was evaluation, which was conducted through weekly tasmi’ and monthly juz advancement examinations. The implementation of these methods was supported by several factors, namely the competence of the ustadz, a conducive pesantren environment, students’ internal motivation, and parental support. However, several obstacles were also identified, including differences in students’ cognitive abilities, physical and psychological fatigue, excessive gadget use, and feelings of boredom and saturation. Overall, the implementation of the talaqi and murojaah methods within the halaqoh system was considered effective in improving students’ learning motivation and Qur’an memorization outcomes.